Differential pain modulation properties in central neuropathic pain after spinal cord injury. Issue 7 (July 2016) - Gruener, Hila; Zeilig, Gabi; Laufer, Yocheved; Blumen, Nava; Defrin, Ruth
Abstract : Abstract: It seems that central neuropathic pain (CNP) is associated with altered abilities to modulate pain; whereas dysfunction in descending pain inhibition is associated with the extent of chronic pain distribution, enhanced pain excitation is associated with the intensity of chronic pain. We investigated the hypothesis that CNP is associated with decreased descending pain inhibition along with increased neuronal excitability and that both traits are associated with spinothalamic tract (STT) damage. Chronic spinal cord injury subjects with CNP (n = 27) and without CNP (n = 23) and healthy controls (n = 20) underwent the measurement of pain adaptation, conditioned pain modulation (CPM), tonic suprathreshold pain (TSP), and spatial summation of pain above injury level. Central neuropathic pain subjects also underwent at and below-lesion STT evaluation and completed the questionnaires. Central neuropathic pain subjects showed decreased CPM and increased enhancement of TSP compared with controls. Among CNP subjects, the dysfunction of CPM and pain adaptation correlated positively with the number of painful body regions. The magnitude of TSP and spatial summation of pain correlated positively with CNP intensity. STT scores correlated with CNP intensity and with TSP, so that the more affected the STT below injury level, the greater the CNP and TSP magnitude. It seems that CNP is associated with altered abilities to modulate pain, whereas dysfunction in descending pain inhibition is associated with the extent of chronic pain distribution and enhanced pain excitation is associated with the intensity of chronic pain. Thus, top–down processes may determine the spread of CNP, whereas bottom–up processes may determine CNP intensity. It also seems that the mechanisms of CNP may involve STT-induced hyperexcitability. Future, longitudinal studies may investigate the timeline of this scenario. Abstract : Pain modulation is differentially altered in central neuropathic pain (CNP); reduced descending inhibition is associated with the extent of CNP distribution, whereas hyperexcitability is associated with CNP intensity.